PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MENGGUNAKAN MODEL ARGUMENT DRIVEN INQUIRY (ADI) UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK PADA MATERI ELASTISITAS DAN HUKUM HOOKE KELAS XI SMA - Novrita, Fitri Dian; Yennita, Yennita; M. Nor, M. Nor (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The learning device developed is a physics learning device using the Argument Driven Inquiry (ADI) model to improve cognitive learning outcomes of class XI SMA student on elasticity and hooke law, consisting of a learning outcomes test instrument. The purpose of this study was to produce a physics learning device using a valid Argument Driven Inquiry (ADI) model and was used to improve cognitive learning outcomes of class XI SMA students on elasticity and hooke’s law. This reseach is expected to be a reference for making innovative learning tools and can be used as a foundation in the teaching and learning objectives can be achieved. This type of research is a Research and Development (R&D) using the 4D model. This research is only limited to the development stage. The research instrument used was the RPP validation assessment sheet, LKPD, and the cognitive learning outcome test instrument used by the validator to assess learning tools. Data analysis in this study used descriptive analysis, by calculating the validity score of each indicator of the learning device. The results showed that the physics learning device using the Argument Driven Inquiry (ADI) model was declared valid with the overall score of the device being 3.58 with a very high category, so it was declarated feasible to be used for teaching in class XI SMA in an effort to improve student cognitive learning outcomes on elasticity and hooke’s law.Key Words: Physics Learning Tools, ADI Model, Cognitive Learning Outcomes, Elasticity and Hooke’s Law.